Juan Marsé: esencialismo simbólico - Domínguez Castro, María Esperanza (Dicenda. Estudios de lengua y literatura españolas, 2008)
Although the narrative of Juan Marsé belongs to narrative realism, it does not offer us a referential reading of a quarter and an epoch, instead it merges historical facts, fiction and rumors that make the «true lie» the literary seed for the «intrahistory» of a community. From there comes our objective: to shed light on the narrative imbrications of the symbolic component that enrich the immediate meaning of discourse and from which emanates the lyricism of a memory blended with imagination. Marsé reflects and distorts some emblems at the foundation of Franco’s repressive regime, made of fear and accusation. Against those, he counters some symbols nested deep in the repressed catalan culture and some class-icons reminding of a polarized social structure. Moreover, the author suggests a personal interpretation of universal symbols. Nevertheless, one of his most original contributions consists of the elaboration of a personal bestiary which embodies some of his narrative’s thematic invariants and reveals the lyrical strength of his symbolic essentialism.